TANGGUNGJAWAB REKTOR SEBAGAI KPA DALAM PENGELOLAAN KEUANGAN PERGURUAN TINGGI NEGERI YANG MENYELENGGARAKAN PENGELOLAAN KEUANGAN BADAN LAYANAN UMUM (PTN PK-BLU) - Sugiharti, Dewi Kania; Ziaurahman, Muhammad; Sechabudin, Sechabudin (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2013)
Universities that apply the concept of Public Service Agency (BLU - PK PTN ) in performing functions as an organ which is engaged in the service infrastructure support through goods or services . As an institution under the auspices of the government and the state budget receives PTN PK - BLU implement mechanisms to acquire goods or services in accordance with the law. However, the procurement process in obtaining goods or services sometimes poses problems that arise as a consequence of the passage of the procurement of goods or services involving the organs in it as PA / KPA , KDP , ULP , and Committee / Receiver Procurement Officer. Rector of the KPA in PK - BLU PTN has the authority to control the organs that carry out the process of procurement of goods / services in the environment . Errors in the procurement process of goods / services performed by the CO and the ULP / Procurement Officer causing state losses due to these errors, either due to negligence or unlawful acts. As the KPA in the process of procurement of goods / services Rector can control the organs in accordance with the authority given. The consequences are acceptable if the authorities ultimately the procurement of goods / services did not heed the warning Rector officials related procurement process of goods / services will receive sanctions. Keywords: Authorized Budget, Financial State.